2020
DOI: 10.1242/dmm.045807
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor death drives retinal dysplasia and neuronal degeneration in a mouse model of ATRIP-Seckel syndrome

Abstract: Seckel syndrome is a type of microcephalic primordial dwarfism (MPD) that is characterized by growth retardation and neurodevelopmental defects, including reports of retinopathy. Mutations in key mediators of the replication stress response, the mutually dependent partners ATR or ATRIP, are among the known causes of Seckel syndrome. However, it remains unclear how their deficiency disrupts the development and function of the central nervous system (CNS). Here, we investigate the cellular and molecular conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…Although RSR has been extensively studied in various models, the mechanisms of the ATR activation and, therefore, the exact roles of ATR regulators in unchallenged replication in vivo are still not completely understood. For example, it was clear that ATR protein stability and function depend on its interaction with ATRIP in human cells ( Cortez et al, 2001 ), however, prior to our recent work ( Matos-Rodrigues et al, 2020a , b ) ATRIP function had not been investigated in vivo . Moreover, while ETAA1 plays an essential role in an ATR-regulated S-G2 checkpoint in immortalized cells ( Saldivar et al, 2018 ), ETAA1 null mice show a mild phenotype of partial embryonic lethality ( Miosge et al, 2017 ).…”
Section: Inactivation Of the Replication Stress Response In Vivomentioning
confidence: 99%
See 4 more Smart Citations
“…Although RSR has been extensively studied in various models, the mechanisms of the ATR activation and, therefore, the exact roles of ATR regulators in unchallenged replication in vivo are still not completely understood. For example, it was clear that ATR protein stability and function depend on its interaction with ATRIP in human cells ( Cortez et al, 2001 ), however, prior to our recent work ( Matos-Rodrigues et al, 2020a , b ) ATRIP function had not been investigated in vivo . Moreover, while ETAA1 plays an essential role in an ATR-regulated S-G2 checkpoint in immortalized cells ( Saldivar et al, 2018 ), ETAA1 null mice show a mild phenotype of partial embryonic lethality ( Miosge et al, 2017 ).…”
Section: Inactivation Of the Replication Stress Response In Vivomentioning
confidence: 99%
“…Microphthalmia has been reported in both Seckel and Nijmegen breakage syndromes ( Figure 1B ). Studies in animal models (discussed in the next sections) suggested that defective cell proliferation and increased cell death may be the cause of microphthalmia following the inactivation of RSR genes ( Yang et al, 2006 ; Rodrigues et al, 2013 ; Matos-Rodrigues et al, 2020a , b ). However, the mechanisms driving eye growth defects in syndromes caused by mutations in RSR-genes are far from being completely understood.…”
Section: Ocular Manifestations In Replication Stress-related Human Syndromesmentioning
confidence: 99%
See 3 more Smart Citations